Null controllability for a degenerate population model in divergence form via Carleman estimates - Fragnelli Genni (Advances in Nonlinear Analysis, 2019)
In this paper we consider a degenerate population equation in divergence form depending on time, on age and on space and we prove a related null controllability result via Carleman estimates.